No Racial Difference in Rehabilitation Therapy across all Post-Acute Care Settings in the Year Following a Stroke - Skolarus, Lesli E. (Stroke, 2017)
BACKGROUND AND PURPOSE: Black stroke survivors experience greater post-stroke disability than whites. Differences in post-acute rehabilitation may contribute to this disparity. Therefore, we estimated racial differences in rehabilitation therapy utilization, intensity and the number post-acute care settings in the first year after a stroke. METHODS: We used national Medicare data to study 186,168 elderly black and white patients hospitalized with a primary diagnosis of stroke in 2011. We tabulated the proportion of stroke survivors receiving physical, occupational and speech and language therapy in each post-acute care setting (inpatient rehabilitation facility, skilled nursing facility and home health agency), minutes of therapy, and number of transitions between settings. We then used generalized linear models to determine whether racial differences in minutes of physical therapy were influenced by demographics, comorbidities, thrombolysis, and markers of stroke severity. RESULTS: Black stroke patients were more likely to receive each type of therapy than white stroke patients. Compared to white stroke patients, black stroke patients received more minutes of physical therapy (897.8 vs. 743.4; p<0.01), occupational therapy (752.7 vs. 648.9; p<0.01), and speech and language therapy (865.7 vs. 658.1; p<0.01). There were no clinically significant differences in physical therapy minutes after adjustment. Blacks had more transitions (median 3, IQR (1–5)) than whites (median 2, IQR (1–5), p < 0.01). CONCLUSIONS: There are no clinically significant racial differences in rehabilitation therapy utilization or intensity after accounting for patient characteristics. It is unlikely that differences in rehabilitation utilization or intensity are important contributors to racial disparities in post-stroke disability.